Weather shocks and child nutritional status in rural Bangladesh: Does labor allocation have a role to play? - Kirara Homma; Abu Hayat Md. Saiful Islam; Masanori Matsuura; Bethelhem Legesse Debela (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2024)
Despite substantial efforts to improve food and nutrient intake in the last decades, child undernutrition remains a daunting challenge, particularly in developing countries' rural areas. Today, frequent extreme weather events harm agricultural production, exacerbating the food shortage problem in these regions. Although off-farm labor is found to be an ex-ante strategy for mitigating weather shocks, little is known about how households' labor reallocation in response to weather shocks is associated with child nutritional status as an ex-post strategy. We investigate how different forms of labor activity mitigate the effect of rainfall shocks on children's nutritional status, using three waves of nationally representative panel data from rural households in Bangladesh, in conjunction with historical monthly precipitation and temperature data. Our findings show that less rainfall during the main cropping season in the year before the survey is associated with a lower weight for age z-score (WAZ score) of children under the age of five years. The findings indicate that there are heterogeneous mitigating impacts of different types of labor allocation affecting the link between rainfall shocks and child health. While maternal labor allocation plays a role as a mitigation factor, household-level labor time and other household members' labor time are not significantly associated with the link between rainfall shocks and child nutritional status. Findings also show that maternal off-farm self-employment mitigates the negative impact of rainfall shortage, whereas maternal on-farm labor exacerbates the rainfall shock impact. Our results therefore underscore the importance of providing sufficient off-farm employment opportunities for mothers and addressing maternal time constraints through targeted policies to cope with rainfall shocks and improve child nutrition.
Keywords: 330; Child nutrition; Labor allocation; Weather shock; Fixed effect model; Bangladesh